2017
DOI: 10.21276/apjhs.2017.4.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Serum Iron profile in Female patients of Melasma-A case control study

Abstract: Background: Melasma is a common acquired pigmentary dermatosis characterized by presence of symmetric, hyperpigmented patches, most commonly seen on the face. It is most commonly seen in young to middle aged females. The exact cause of melasma is not known, however a number of factors have been implicated in its etiopathogenesis. The effect of body iron stores on melasma is not exactly known. Although iron overload has been seen to affect skin pigmentation, effect of low body iron stores on skin pigmentation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
6
1
2
Order By: Relevance
“…In the present study, all variables were tested for association with MASI, but the results showed no significance. On the contrary to these results, Qazi et al stated a positive correlation between MASI score and iron profile [17], which could be also due to the lower mean serum iron in the study by Qazi et al, while only reduced iron storage was detected in the patients of the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the present study, all variables were tested for association with MASI, but the results showed no significance. On the contrary to these results, Qazi et al stated a positive correlation between MASI score and iron profile [17], which could be also due to the lower mean serum iron in the study by Qazi et al, while only reduced iron storage was detected in the patients of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the mean age of the groups had significant differences, which could also be attributed to different iron profile, so we adjusted the analysis regarding the age difference. The study by Qazi et al (2017), comparing 70 nonpregnant women with melasma and the control group, showed a lower mean serum iron and ferritin levels, beside a higher TIBC in the case group [17]. These results showed a higher frequency of anemia and lower iron storage in women with melasma, which was consistent to the results of the present study, although the Hb and TIBC levels did not differ between the groups in our study and lower iron storage, was indicated by the lower mean serum iron and higher frequency of below normal range ferritin level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Iram Qazi et al also showed patients with melasma had low body Iron stores compared to the control population indicating a possible role of iron deficiency in the etiopathogenesis of melisma. 22 In our study, we found that about 80% of women and 20% of men have melasma. Most studies conducted in India showed almost similar results.…”
Section: Discussionmentioning
confidence: 50%